TECHNOGENIC DANGER ‑ RADIOACTIVE CONTAMINATION OF PLANT PRODUCTS - Реус, Ирина; Кудрявицкая, Алина; Пилипко, Алина (SWorldJournal, 2021)
The important task of radiological defence is minimization of the dose loading on a population. His decision is possible due to creation rows of events, that is sent to prevention, liquidation and reduction of possible consequences of contamination of pro